Online art therapy practice and client safety: a UK-wide survey in times of COVID-19. Issue 4 (1st October 2020) - Zubala, Ania; Hackett, Simon
ABSTRACT: Background: The COVID-19 pandemic enforced a sudden change in practice and a move into online delivery for many art therapists in the UK, often with minimal guidance and little previous experience of remote delivery. Aims: To explore ways in which practitioners adapted practice to ensure continuity of service and client safety at distance. Methods: An online survey designed to explore practitioners' perspectives and experiences of using digital technology in art therapy sessions with clients. Results: Vast majority of 96 respondents reported having worked with clients online as a result of the pandemic. The respondents expressed concerns about safety of practice and their own confidence in delivering therapy remotely. Increased clinical supervision, specialist training, and support from colleagues were valued in the rapid transitioning to online practice. Conclusions: A snap shot of art therapists' responses to a need to adapt their practice due to the pandemic is presented, including approaches to working with technology and strategies that therapists employed to ensure their clients' and own safety. Implications for practice/policy/future research: Being able to offer a safe environment for clients is a priority for practitioners. Further research, guidance and training might offer the support needed for developing a suitably safe online practice. Plain-language summary: Art therapists practice in the UK has until recently been primarily face to face, being in the same space with their clients while offering art therapy sessions and being able to observe how they use art materials to create artwork. Due to the COVID-19 pandemic many UK-based art therapists needed to adopt creative approaches to make a rapid shift to delivering therapy online, often with minimal guidance and little previous experience of remote delivery. We have conducted an online survey to explore how art therapists have made changes in their practice and what has supported them in the process. 96 art therapists took part in the survey and shared their experiences and strategies that they have adopted to rapidly move to connecting with clients remotely. They have shared that safety of their clients was of key importance and showed how this concern has guided their transition into online practice. The respondents mentioned that clinical supervision and support from colleagues were helpful in ensuring safety of their clients and themselves. Since online art therapy is expected to continue beyond the pandemic, more research in the area is needed as well as guidance and training for art therapists that would increase their confidence in working with clients online.